Genotypic profile and antimicrobial resistance of avian pathogenic Escherichia coli - Spricigo, Ana Carolina; Peripolli, Vanessa; Costa, Paulo Mafra de Almeida; Millezi, Alessandra; Sperandio, Jhonatan (Revista de Ciências Agroveterinárias, 2024)
Avian pathogenic Escherichia coli (APEC) is responsible for several anatomopathological conditions in poultry, which cause great damage to the poultry sector. This study aimed to evaluate the pathogenicity of E. coli strains isolated from broiler chickens and to perform in vitro tests on strains classified as APEC to identify their capacity to form biofilms and sensitivity to antimicrobials routinely used in the poultry breeding process. Sixty E. coli poultry isolated were used in this study. The real-time Polymerase Chain Reaction (PCR) test identified that 100% of the isolates had the hlyF and ompT genes, 98.3% the iroN and iss genes, and 83.33% the iutA gene, being all the evaluated strains classified as APEC. In the in vitro evaluations regarding the formation and characterization of biofilms, the APEC samples were characterized as 71.66% weakly biofilm-forming. The antibiotic sensitivity test showed that the highest resistance percentages were found in the molecules of oxytetracycline, with 33%, and doxycycline, with 31.66%, but about 58,33% of the samples had a profile of multi-resistance to antimicrobials. Further studies are needed to better characterize APEC virulence genes and multi-drug resistance, given their impact on poultry health/production and potential risk to human health.